Realismo e pluralismo: a filosofia da ciência de Karl R. Popper - Romanini, Mateus (2012)
This work aims to provide an interpretation of Karl Raimund Popper s work concerning two problems and the solutions he proposed to them. Firstly, we will deal with the problems emerging from the debate about which entities can be considered real, namely, whether and how abstract entities interact with the physical world. Popper rejects monist and dualist positions because both of them lead to determinism. So, in order to solve this problem, he proposes a tripartite notion of reality, claiming that reality is the interaction of three worlds: the physical world (World 1), the world of mental states (World 2) and the objective world of abstract entities (World 3). World 3 is inhabited by different types of theories, many of which are very similar to scientific theories, even though they do not belong to the empirical sciences. This account leads to the second problem treated in this work. The problem of demarcation concerns the demarcation of science domains, distinguishing it from the domain of non-scientific theories. Popper solves this problem by giving up the use of induction, because he considers it to be invalid and it would lead science to irrationalism. Instead, he proposes a deductive method of trial and error. Thus, Popper criticizes Verificationism, taken by him as a demarcation criterion which uses inductive logic, and proposes instead Falsificationism. The aim of this work is to unify these two theories demonstrating that one can be interpreted as a consequence of another, seeking to present Popper s account more widely and demonstrating the importance of working them together, in order to comprehend some aspects of the author s theory, such as the notions of truth and knowledge growth.